2014
DOI: 10.1142/s0192415x14500578
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Litsea coreana Decreases TNF-α Secretion from Peritoneal Macrophages in Adjuvant-Induced Arthritis Rats via UPR Pathway

Abstract: Macrophages play a crucial role in rheumatoid arthritis (RA). Their activation is the initial step of RA. This study was designed to detect the effects of total flavonoids from Litsea coreana Levl. (TFLC) on the complete Freund's adjuvant-induced (CFA-induced) arthritis (AA) in rats and to explore whether inflammatory cytokines were induced by the IRE1/mTORC1/TNF-α-dependant mechanism in peritoneal macrophages. In vivo, our data indicated that TFLC (100, 200 mg/kg, i.g. × 10 days) could significantly suppress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…For example, some Xalacom ® studies [13, 14, 25, 26] fell into this category. In addition, studies with an exclusively Asian population were excluded [27]. Open-label or investigator-masked (single-masked) studies were not included due to the potential problem with bias.…”
Section: Methodsmentioning
confidence: 99%
“…For example, some Xalacom ® studies [13, 14, 25, 26] fell into this category. In addition, studies with an exclusively Asian population were excluded [27]. Open-label or investigator-masked (single-masked) studies were not included due to the potential problem with bias.…”
Section: Methodsmentioning
confidence: 99%
“…Together, TFLC had a therapeutic effect on AA rats via decreasing the production of inflammatory cytokines and inhibiting the expression of MMP-9 (Wang et al 2007(Wang et al , 2008. Another study on AA demonstrated that TFLC (100 mg/kg) diminished secondary paw swelling and suppressed serum levels of TNF-a and IL-1b, and reduced the expression of mTOR complex 1 and TNF-a in peritoneal macrophages (Zhong et al 2014). In collagen II-induced arthritis rat model, TFLC (50 mg/kg) inhibited the paw swelling and increased body weight of rats.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…The IRE1α-XBP1s axis can splice to induce toll-like receptor-dependent cytokine secretion and maintain the autocrine cycle of FLS activation ( 72 ). Flavonoids from Litsea coreana were found to inhibit IRE1/mTORC1/TNF-α-regulated inflammatory responses triggered in peritoneal macrophages of CIA mice and ameliorated arthritis in a dose-dependent manner in CIA mice ( 73 ). In a study of peripheral blood mononuclear cells (PBMCs) from RA patients, it was found that the expression of GRP78, IRE1, and XBP1 was significantly increased in RA patients.…”
Section: Ers In Ramentioning
confidence: 99%